COMPARATIVE COMPOUND SENTENCE WITHOUT CONJUNCTIONS IN LANGUAGES - Dadabaeva Shirin (Zeta Repository, 2023)
The article gives information on the type of sentence in comparison in Uzbek and English languages. This sentence is connected by tone using comma and is given as separate type of composite sentence in Uzbek. Whereas it is connected by semicolon and is referred as compound sentence in English